ARMENIAN AMERICAN MENTAL HEALTH ASSOCIATION OF CALIFORNIA: GENESIS, MISSION, VALUES, GOALS, STRATEGIES, AND ACCOMPLISHMENTS - Kaftarian, Sh. (Արդի հոգեբանություն, 2019)
California is a large and densely populated state, comprised of 58 counties, which are administrative divisions of the State. Los Angeles County is the largest county in California, with large Armenian American (AA) communities within its borders. LA County’s Department of Mental Health (LACDMH) in turn is the largest county-based mental health department in California.